Speech pathology services for people with aphasia: what is the current practice in Singapore?. (April 2014) - Guo, Yiting Emily; Togher, Leanne; Power, Emma
Abstract Purpose: This study reports on current provision of aphasia services by speech pathologists in Singapore. Method: A 44-item web-based survey was conducted looking into areas of service delivery, assessment, cultural and linguistic adaptations, clinical approaches, education of clients, recovery, goal setting and discharge as well as scope and challenges to practice. Results: A total of 36 surveys were completed representing approximately 86% of the potential target population. The intensity of aphasia services provided was well below that recommended by the literature. Participants reported embracing approaches to aphasia rehabilitation that spanned across the ICF domains. Numerous challenges were reported in providing aphasia services. These included the lack of locally relevant resources for aphasia, lack of family support and patient motivation, manpower shortages as well as barriers such as transport and cost restricting access to services. Conclusions: This research reveals several findings with considerable implications for practice planning and future direction in aphasia rehabilitation. There is a need for the development of locally relevant aphasia resources to enable comprehensive provision of aphasia services. In addition, further investigation is required to tackle the resource challenges faced by the profession and improve community support for people with aphasia. Implications for Rehabilitation Speech pathology services for aphasia in Singapore This article has identified the challenges of providing aphasia services in the Singapore context. Further investigation is required to address the key issues to improve aphasia services in Singapore. This includes developing locally relevant resources, looking at means like telerehabilition to tackle resource challenges, and improving community support for people with aphasia.